Reflections on the Future of University Outreach in Mexico - Rosas González, Samuel (2025)
This essay aims to contribute to the debate on the role of university outreach in Mexico. It is based on the premise that the university is in crisis due to the internal dispute between two projects seeking to dominate and reorient its social function. The first one, with a public character, maintains that knowledge should be helpful in society. The second one, with a commercial character, considers that knowledge should promote entrepreneurial logic. In this context, what role does university outreach play? What is its regulatory status? What are the criteria for connecting with society? These questions call us to reflect on the limits and scope of university outreach as a possibility for consolidating a university project that, through alliance and coordination with society, responds creatively to the challenges posed by the present and the future.